THE EFFECT OF CARROT PUREE ADDITION FOR QUALITY OF REBON SHRIMP (Acetes sp.) CRACKERS KAKI NAGA - Jesika Gembira A Rajagukguk; Suparmi Suparmi; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe purpose of the research was to observe the effect of carrot puree addition on the quality of rebon shrimp (Acetes sp.) crackers kaki naga and to determine the optimum amount of carrot puree added to produce the best rebon shrimp crackers kaki naga. The method used was an experiment by non-factorial of completely randomized design (CRD) to conduct the treatment of carrot puree addition, consisted  of 4 levels, (0, 10, 20, 30 gs) in 3 repetitions. The parameters observed included the hedonic evaluation (appearance, smell, taste, and texture) and the proximate value (water content, protein, crude fiber, and carbohydrates). The results showed that the addition of carrot puree with different amounts had a significant effect to the crackers produced. The most preferred product was addition of 20 gs carrot puree shown by the value of appearance 7.0, smell 6.2, taste 6.7, and texture 6.6. The chemical analysis were showing the value of water content 50.36%, protein content 3.19%, crude fiber content 5.69%, and carbohydrates content 12.83%. All products have fulfilled the standard quality of crackers determined by SNI 7759: 2013.Keywords: carrot puree, crackers kaki naga, rebon shrimp (Acetes sp.),